Assessing the risks of haemolysis as an adverse reaction following the transfusion of ABO incompatible plasma-containing components - a scoping review - McCullagh, J; Cardigan, R; Brunskill, SJ; Bullock, T; Doree, C; Estcourt, L; Huish, S; Sandercock, J; Green, L (Elsevier, 2022)
Background: The limited supply of universal plasma has resulted in transfusion of ABO incompatible plasma to patients. As the need to implement whole blood transfusion in pre-hospitals setting rises, the lowest cut-off for anti-A/anti-B that does not cause haemolysis remains unknown. In this first scoping review, we aimed to determine the lowest ABO titre and volume reported in the literature to cause haemolysis from ABO incompatible plasma transfusions (plasma, platelets, cryoprecipitate, and whole blood).